2021
DOI: 10.1016/j.molp.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of agronomically important genes in outcrossing crops using OutcrossSeq

Abstract: Many important crops (e.g., tuber, root, and tree crops) are cross-pollinating. For these crops, no inbred lines are available for genetic study and breeding because they are self-incompatible, clonally propagated, or have a long generation time, making the identification of agronomically important genes difficult, particularly in crops with a complex autopolyploid genome. In this study, we developed a method, OutcrossSeq, for mapping agronomically important loci in outcrossing crops based on whole-genome low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 85 publications
0
38
0
Order By: Relevance
“…Yamamoto et al (2020) developed a low-coverage RADseq-based genotyping method, ngsAssocPoly, and detected loci associated with skin colour and internode length by calculating allele dosage probabilities. Chen et al (2021) created Outcross-ingSeq, in which 1807 F 1 progenies were barcoded and wholegenome resequenced with 1.5-time coverage for each individual to identify loci controlling vein colour, leaf shape and number of storage roots. These low-coverage NGS methods are costefficient but labour-intensive because the preparation of barcoded sequencing libraries is necessary for each progeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al (2020) developed a low-coverage RADseq-based genotyping method, ngsAssocPoly, and detected loci associated with skin colour and internode length by calculating allele dosage probabilities. Chen et al (2021) created Outcross-ingSeq, in which 1807 F 1 progenies were barcoded and wholegenome resequenced with 1.5-time coverage for each individual to identify loci controlling vein colour, leaf shape and number of storage roots. These low-coverage NGS methods are costefficient but labour-intensive because the preparation of barcoded sequencing libraries is necessary for each progeny.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al. ( 2021 ) created OutcrossingSeq, in which 1807 F 1 progenies were barcoded and whole‐genome resequenced with 1.5‐time coverage for each individual to identify loci controlling vein colour, leaf shape and number of storage roots. These low‐coverage NGS methods are cost‐efficient but labour‐intensive because the preparation of barcoded sequencing libraries is necessary for each progeny.…”
Section: Discussionmentioning
confidence: 99%
“…One primary step of NGS data analysis is to do genotyping from the short reads data to generate the genome variation map. There are already some excellent pipelines like SNPtools (Wang et al 2013),GotCloud (Jun et al 2015) and OutcrossSeq (Chen et al 2021) that provide the whole work ow from raw sequence data to imputed genotype matrix. However, most populate software and pipelines are devoted to tackle the model species genome sequence data.…”
Section: Introductionmentioning
confidence: 99%
“…It provides a common model for understanding the genetic basis of color mutants ( Zhu et al, 2015 ; Sun et al, 2018 ). The co-expression network analysis (WGCNA) ( Langfelder and Horvath, 2008 ) and the knowledge-based identification of pathway enzymes (KIPEs) ( Pucker et al, 2020 ) based on the genome-wide and transcriptome-wide analyses have been applied to identify the tissue-specific regulation of anthocyanin biosynthesis ( Tombuloglu et al, 2013 ; Liu et al, 2018 , 2020 ; Iorizzo et al, 2020 ; Qin et al, 2020 ; Zhang et al, 2020 ; Chen et al, 2021 ; Parra-Galindo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that IbMYB1-2 plays a vital regulatory role in anthocyanin accumulation in storage roots ( Tanaka et al, 2011 ), but it is not necessary in all varieties for the expression of IbMYB1 ( Kim et al, 2010 ; Li et al, 2019 ; Zhang et al, 2020 ). A major locus of chromosome 5, where IbMYB1 genes are located, has been shown to have a large effect on the color variation of shoots ( Chen et al, 2021 ). We speculated that more IbMYB1 members with genetic complementation may be involved in the regulation of anthocyanin biosynthesis in cultivated species.…”
Section: Introductionmentioning
confidence: 99%